Alternative Dispute Resolution: Mediation In Terms Of Dispute Resolution For Aircraft Accident Compensation For Aircraft Product Defects(Case Study of Sriwijaya Air Sj182 Plane Accident) - Priaardanto, Columbanus; Amad Sudiro (JURNAL USM LAW REVIEW, 2025)
This study discusses mediation strategies as a legal instrument in overcoming the obstacles of the doctrine of forum non conveniens in international lawsuits for compensation due to aircraft accidents, especially in product defect cases against aircraft manufacturers in the United States. Non-conveniens forums are often an obstacle for victims from other countries to access justice through the U.S. legal system, as courts may dismiss lawsuits if alternative forums are deemed more appropriate. In this context, mediation serves as an efficient, flexible, and more humane dispute resolution mechanism. The Lion Air JT 610 accident case study is used as a prime illustration, where the victim's family managed to obtain compensation through mediation with Boeing, despite the potential lawsuit being dismissed based on a non-conveniens forum. This research shows that mediation can be an effective litigation strategy to speed up settlement, avoid complex litigation processes, and strengthen the victim's position in cross-jurisdictional negotiations. The research method used is normative juridical with a case approach and legal comparison. Data were obtained through literature review, analysis of legal documents, and review of court decisions and mediation practices in U.S. federal courts. The results of the study recommend the need to harmonize cross-border mediation procedures and strengthen access to alternative dispute resolution mechanisms for victims from developing countries.